Dinâmica do arsênio no sistema solo - água - arroz na América do Sul: distinções fisiológicas entre cultivares e ocorrência em grãos comerciais - Farias, Júlia Gomes (2016)
Rice is the main source of inorganic arsenic (Asi), a carcinogenic substance, in the human diet. In this sense, there is great interest in reducing the accumulation of As in rice grains. To achive this, field management / rice processing and study of different cultivars have been explored. Globally, many countries that consume rice don t produce it, or even specifics regions of a producer country. As to maintain the rice consumption these regions have to import rice, the identifycation of regions with low As is an important option to ensure food security for the consumers. However, the location of As free areas seems to be an incomplete solution; as there is a large demand for rice and the already considerable number of areas described as contaminated. Thus, it is necessary to use a set of information able to describe As levels in different areas, comparing cultivars, including specific mechanisms of tolerance and low translocation, besides the description of side effects such as levels of other minerals present in the grain and effect of soil management on grain quality. Given the above, this study aimed to evaluate commercial samples of rice in Latin America, as well as samples collected in the field under different managements of water, fertilizer and land use; in addition it was used short-term experiments in greenhouse were performed to evaluate morphophysiological parameters in different cultivars. There is a large discrepancy regarding As concentration among the different regions tested. Although the genetic factor (cultivar) has an effect on As concentration in grain, environmental and management factors are decisive. Apparently the cultivar BR-IRGA 409 presents a large susceptibility to As, also presenting a lower translocation to grains while cultivars described as tolerant had a higher accumulation of this element. The phosphorus use efficiency and the concentration of non-protein thiols appear to be related to tolerance, being highly pronounced in tolerant cultivars. Finally, As has a high potential to genotoxic and oxidative stress, and the main abnormality observed was the presence of micro-nuclei.